A case report of a COPD patient presented in severe metabolic alkalosis - Shrestha, Ashish; Gurung, Naresh; Karthak, Ashish; Bhattarai, Sanjeet; Lama, Rakesh; Shrestha, Utsav Kumar; Khanal, Kishor; Ghimire, Anup; Regmi, Ashim; Shrestha, Sanjeet Krishna (Nepalese Respiratory Journal, 2022)
Chronic Obstructive Pulmonary Disease (COPD) patients generally present with respiratory acidosis and type 2 respiratory failure. Here we present a case of 65 years old female, who is a known case of COPD and presented in our emergency department with severe metabolic alkalosis (pH 7.730, HCO3- greater than 99.9mmol/l). She was referred from other center after the development of seizure. Urinary sodium was sent which indicated the cause of metabolic alkalosis was contraction alkalosis; we then treated the patient with IV fluids, antibiotics and Mechanical Ventilator. Arterial Blood gas analysis was initially done every 4 hours till the pH was corrected. After pH was corrected the patient was extubated to intermitted Non Invasive Ventilation (NIV) for type 2 respiratory failure. With pulmonary rehabilitation we could discharge the patient with inhalers; without the need for NIV or supplementary oxygen. This is one of the rare cases where the patient presented with a very high bicarbonate level, high partial pressure of carbon dioxide in arterial blood, and high pH. The patient was successfully managed with IV fluids and mechanical ventilation.